Study of psychosocial aspects contributing to stress among women with primary infertility - Manikkam, Banumathy; Bhargavi, Vijaya (International Journal Of Community Medicine And Public Health, 2020)
Background: Infertility remains a global problem since ages and lot of stigma in society even in the modern era. The burden of psychosocial stress in primary infertility is overwhelming, still there is limited literature regarding this. Methods: We conducted a prospective study on 300 primary infertile women to determine the prevalence of psychosocial stress and the contributing factors. Data was collected using a semi structured questionnaire through a one-one interview, after narrating the purpose analysed the relationship of various psychosocial factors to infertility related stress. Results: In the present study, female factor 41%, 25% had male factor, 9% couple with combined factor and 25% with unexplained infertility. Polycystic ovarian syndrome was the most common, 25.6%, and tubal factor 13.3%. The sperm abnormalities and oligozoospermia in 20.3%. Earlier 52% had undergone ovulation induction, 38% had intrauterine insemination and only 10% undergone in vitro fertilization. 23% women and 4% men suffered psychological trauma in the past, 4% women had already been treated for psychiatric problem. We found higher scores for failed period, mind distraction, avoiding social gatherings. Parenthood desire seen in 82%, 8% for continuation of progeny, 7.6% for future security and 2.3% for social obligation. 53% were willing to adopt on failure of treatment. The prevalence of psychosocial stress was 70% in present study. Conclusions: Understanding the psycho social factors associated with stress helps to alleviate and improve the quality of life. Public health awareness programs and coping strategies are the need of the hour. Encouraging adoption will solve the twin problems of infertility and abandoned kids.